Redesign of Prestressed Concrete Structures Using the Post Tension Method: A Case Study of the Construction of Laves Mall Surabaya - Mahendra Nata, Eric Vianto; Komara, Indra; Susanti, Eka; Pertiwi, Dewi (Universitas Tribhuwana Tunggadewi Malang, 2022)
In building construction, prestressed concrete is used for large spans and to increase capacity. One of them is the 16 meters long Lakes Surabaya Mall project. An important parameter is the effectiveness of the design, especially determining the parameters of the cross-sectional property. In this study, the redesign technique was used to assess the current condition in the hope that it could be modeled more effectively using cross-sectional dimensions. The design was evaluated theoretically using the concept of direct and indirect prestressing, then numerically verified using SAP2000. Prestressed beam with low relaxation PC60×12cm A416 grade 250 in the existing condition is modified using a lower dimension of 50×10cm A416 but has a grade value of 270, which is more extensive. The same data were used for criteria such as 35 MPa concrete quality, 100% load distribution factor, and 75% tendon stress percentage. The inspection results show that the transfer and service conditions are 10% smaller than the existing cross-section. A combined direct and indirect prestress loss of 19% still meets the design code.ABSTRAKDalam bidang konstruksi bangunan, beton prategang digunakan untuk bentang besar dan untuk meningkatkan kapasitas. Salah satunya adalah pada proyek Mall Lakes Surabaya sepanjang 16 meter. Parameter penting adalah efektivitas desain, terutama menentukan parameter properti penampang. Dalam penelitian ini, teknik desain ulang digunakan untuk menilai kondisi saat eksisting dengan harapan dapat dimodelkan lebih efektif dari penggunaan dimensi penampang. Desain dievaluasi secara teoritis menggunakan konsep prategang langsung dan tidak langsung, kemudian diverifikasi secara numerik dengan SAP2000. Balok prategang dengan relaksasi rendah PC60×12cm A416 grade 250 pada kondisi eksisting dimodifikasi menggunakan dimensi lebih rendah yaitu 50×10cm A416 akan tetapi memiliki nilai grade 270, yakni lebih besar. Data yang sama digunakan untuk kriteria seperti kualitas beton 35 MPa, faktor distribusi beban 100%, dan persentase tegangan tendon 75%. Hasil pemeriksaan menunjukkan bahwa kondisi transfer dan service 10% lebih kecil dari penampang eksisting. Dengan gabungan kehilangan prategang langsung dan tidak langsung sebesar 19%, yang mana masih memenuhi kaidah desain.